κοτυλήρυτον ἔρρεεν αἷμα: Homer, Iliada, 23. 34 - Burliga, Bogdan (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2016)
The subject of the article is a short passage in Homer’s Iliad, Book 23. 30–34, depicting Achilles’ slaughtering of the various domestic animals and the dinner that follows (23. 55–58). The controversy focuses on the problem whether the killing in question was a sacrifice or not.